The Blended Language Learning Course in Taiwan: Issues and Challenges of Instructional Design - Liu, Gi-Zen (Case Studies in Language Curriculum Design, 2011)
Humans use language in various forms for communication for many purposes (Graddol, 2004; Szathmary & Szamado, 2008). We are living in a networked society in which information and communication technologies (ICT) are used in many situations, fields, and contexts to facilitate language learning, including the first and other languages. Technology enhanced language learning (TELL) is a trans-disciplinary field that has been influencing human language development in various academic subjects and areas for more than half a century. Since the 1990s, ICT-embedded language learning has been the most widely used form of TELL. In addition, the English language has been identified as "power on the Internet" (Flammia & Saunders, 2007), and in non-English-speaking countries English as a foreign language (EFL) or English as an international language (EIL) dominates the international use and spread of information and knowledge in many fields and contexts (Crystal, 2003; Graddol, 2000, 2004, 2006). Innovative ICT (Becta, 2004; Hill & Vasudevan, 2008) has opened the door for exploring culture-rich language learning materials, practicing receptive and productive language abilities, and promoting frequent language use in two-way communication.